Functional Pancreatic Sphincter Dysfunction in Children: Recommendations for Diagnosis and Management. Issue 6 (December 2019) - Lin, Tom K.; Fishman, Douglas S.; Giefer, Matthew J.; Liu, Quin Y.; Troendle, David; Werlin, Steven; Lowe, Mark E.; Uc, Aliye
ABSTRACT: Objective: Functional pancreatic sphincter dysfunction (FPSD), previously characterized as pancreatic sphincter of Oddi dysfunction, is a rarely described cause of pancreatitis. Most studies are reported in adults with alcohol or smoking as confounders, which are uncommon risk factors in children. There are no tests to reliably diagnose FPSD in pediatrics and it is unclear to what degree this disorder contributes to childhood pancreatitis. Methods: We conducted a literature review of the diagnostic and treatment approaches for FPSD, including unique challenges applicable to pediatrics. We identified best practices in the management of children with suspected FPSD and formed a consensus expert opinion. Results: In children with acute recurrent pancreatitis (ARP) or chronic pancreatitis (CP), we recommend that other risk factors, specifically obstructive factors, be ruled out before considering FPSD as the underlying etiology. In children with ARP/CP, FPSD may be the etiology behind a persistently dilated pancreatic duct in the absence of an alternative obstructive process. Endoscopic retrograde cholangiopancreatography with sphincterotomy should be considered in a select group of children with ARP/CP when FPSD is highly suspected and other etiologies have been effectively ruled out. The family and patient should be thoroughly counseled regarding the risks and advantages of endoscopic intervention. Endoscopic retrograde cholangiopancreatography for suspected FPSD should be considered with caution in children with ARP/CP when pancreatic ductal dilatation is absent. Conclusions: Our consensus expert guidelines provide a uniform approach to the diagnosis and treatment of pediatric FPSD. Further research is necessary to determine the full contribution of FPSD to pediatric pancreatitis.